GAMBARAN MAKROSKOPIK LIMPA TIKUS (Rattus norvegicus) PADA PEMBERIAAN EKSTRAK ETANOL DAUN GINSENG (Talinum paniculatum (Jacq.) Gaertn) YANG DIINDUKSI OVALBUMIN - Multazania, Multazania; sahab, Fitria; Muarsih, Ahmad Juniardhy; Ashar, Muhammad Affan; Emelda, Andi; Putra, Bayu; Santi, Irma (Makassar Pharmaceutical Science Journal (MPSJ), 2025)
Fameflower Leaves (Talinum paniculatum (Jacq) Gaertn) are medicinal plants that communities have traditionally used due to their active compounds, such as saponins, flavonoids, tannins, triterpenes, sterols, and polyphenols found in both the leaves and roots. This study aimed to determine the dose of ethanol extract of fameflower leaves affecting the histology of the spleen in male rats (Rattus norvegicus) following ovalbumin antigen stimulation, as well as to observe changes in the spleen tissue structure after the extract treatment. The study used 20 Wistar rats divided into four groups. The rats were first adapted for 2 weeks and then fasted for 8 hours before the treatment—a group I served as the standard control. Group II was induced with ovalbumin antigen. Groups III and IV were induced with the antigen, and the ethanol extract of fameflower leaves was administered at doses of 0.4g/kgBW and 0.8g/kgBW, respectively. The extract was administered orally for 7 days to the test animals. On day 8, the test animals were sacrificed, and their spleens were harvested for histological preparation using the Hematoxylin-Eosin staining method. Microscopic observation showed no histological damage in the spleen, such as inflammation, degeneration, congestion, hemorrhage, or necrosis. Therefore, it can be concluded that the ethanol extract of Bugis Ginseng leaves did not affect the spleen of rats at doses of 0.4g/kgBW and 0.8g/kgBW